44.1k views
2 votes
Find the radius of the circle given by this equation:

Find the radius of the circle given by this equation:-example-1

1 Answer

5 votes

Answer:

8

Explanation:

We know that

Equation


{x}^(2) + {y}^(2) + 2gx + 2fy + c = 0

Represents the equation of Circle

where


radius = \sqrt{ {g}^(2) + {f}^(2) - c }

On comparing the given equation with general Equation of Circle

we get


g = - 5


f = 3


c = - 30

On substituting these values We get


radius = \sqrt{ { (- 5)}^(2) + {3}^(2) - ( - 30) }


radius = √(25 + 9 + 30 ) = √(64 ) = 8


radius = 8

User Jonathan Spiller
by
5.2k points